Ukraine's fiscal developments and needs for economic recovery, reconstruction and European integration - Tetiana Bogdan (The Vienna Institute for International Economic Studies (wiiw), 2024)
This policy report provides an up-to-date assessment of Ukraine's fiscal situation and locates the analysis in the longer-term context of the needs to keep the state viable in the current war situation, but also to deal with the challenges of reconstruction after the war and on its path towards EU accession. It studies in detail the structure and evolution of Ukraine's budget revenue in a time of war and reveals social and economic needs of a war-torn country in the areas of social protection, housing recovery, health care and education reforms, transport infrastructure, energy sector, industry and agriculture. It outlines the necessity to increase public revenue and considers different tax policy initiatives for funding a reconstruction program and restoring fiscal sustainability. The study elaborates a methodology for assessment and medium-term projections of consolidated budget expenditure, which are required for meeting Ukraine's recovery and reconstruction needs. It also provides budget deficit projections and gross financing needs assessments over the period 2024-2028. It shows the substantial foreign financing gaps for 2025-2026 and following years and analyses in details the external and, especially, EU financial support pledged to Ukraine. Finally, it discusses the staged EU accession model in the context of addressing reconstruction challenges and Ukraine's progressing on the path to EU membership.
Keywords: H3; H5; H6; O52; O11; 330; Ukraine's economic reconstruction; Ukraine's fiscal situation; Ukraine's external financing needs; EU staged accession model